Tindak Pidana bagi Orang yang Berkebutuhan Khusus (Penyandang Disabilitas) dalam Perspektif Hukum Islam: Criminal Offenses for People with Special Needs (Person with Disabilities) in the Perspective of Islamic Law - Muhammad Taufan Djafri; Ridwan, Ridwan; Mu’adz Hasan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This research aims to find out and understand how punishment according to Islamic law is for people with special needs when committing a crime. This research is a type of qualitative research using library research methods. The legal materials are analyzed using a deductive method, namely a logical approach to determine a conclusion based on an analytical study of writing a Sharia perspective on the context of the problem using a normative juridical approach. The results of this research found that the judge's consideration is one of the most important aspects in determining the realization of the value of a judge's decision which contains justice and contains legal certainty, besides that it also contains benefits for the parties concerned so that the judge's consideration must be addressed carefully, well, and carefully. That the determination of criminal law by people with special needs who do not fulfill the elements previously mentioned means that in Islamic law they are not held responsible for their actions. However, in Islam, people with disabilities are not completely free from punishment. Because other people's property and souls are guaranteed by sharia'. Therefore, criminal perpetrators with disabilities are still held civilly liable. In Islamic law it is called diyat.